Pengaruh Model Numbered Head Together Terhadap Kemampuan Berpikir Kritis Dalam Pembelajaran Penjas Kelas V Di Sekolah Dasar - Putra, Reyhan Aulia; Matsuri, Matsuri (Universitas Sebelas Maret, 2025)
Reyhan Aulia Putra. K7121236. Pembimbing I: Dr. Matsuri, M.Pd. PENGARUHMODEL NUMBERED HEAD TOGETHER TERHADAP KEMAMPUANBERPIKIR KRITIS DALAM PEMBELAJARAN PENJAS KELAS V DISEKOLAH DASAR SE-GUGUS V KOKAP TAHUN AJARAN 2024/2025.Skripsi, Surakarta: Fakultas Keguruan dan Ilmu Pendidikan Universitas SebelasMaret. Surakarta, Mei 2025Learning refers to the efforts made by educators to encourage students toengage in learning activities. Elementary Schools (SD) provide basic education andhelp students develop essential 4C skills: creativity, critical thinking,communication, and collaboration. Critical thinking is especially important inphysical education, which involves psychomotor processes requiring analysis andevaluation. Learning models at the elementary level can be adapted to matchstudents' developmental stages, making the material easier to understand. TheNumbered Heads Together (NHT) model promotes collaboration and activeparticipation, thereby enhancing critical thinking skills. This study aims to examinethe effect of the NHT model on critical thinking in physical education. A quantitativeapproach with a quasi-experimental method was used. The research took place atSDN 1 Pripih, SDN Gambir, and SDN Banjaran, involving 46 fifth-grade students inCluster V of Kokap District. Critical thinking skills were categorized as very critical,critical, quite critical, less critical, and very less critical. Hypothesis testing using theIndependent Sample T-test showed a significance value (Sig. 2-tailed) of 0.001 withtcount > ttable (11.924 > 2.045). It was concluded that the implementation of theNumbered Heads Together model positively affects critical thinking skills inphysical education.Kata Kunci: Numbered Head Together, Kemampuan Berpikir kritis, Elementary School